Neuroprotective Effect of IQUP-B Against Scopolamine-Induced Cognitive Impairment in Wistar Rats - Mangalampalli, Kezia; Kolusu, Aravinda Sai; Ramineni, Hrushik Kowtinya; Mudigonda, Harshitha; Devarakonda, Surya; Samudrala, Pavan Kumar (International Journal of Pharmaceutical Investigation, 2025)
Background Cholinergic neurons in the brain and hippocampus appear to be most affected in the early stages of Alzheimer's Disease (AD). Cognitive impairment has been induced in rodents for many years with the muscarinic receptor antagonist scopolamine. In this work, we assessed the polyherbal formulation extract’s ability to protect against scopolamine induced cognitive impairment and oxidative stress. Materials and Methods Scopolamine (3 mg/kg, i.p.) was given to rats 1 hr after pre-treatment with IQUP-B (400 mg/kg, p.o.,). The NORT, Y-maze, and Morris water maze tests were used to assess memory performance after 30 min of the scopolamine injection. On the sixteenth day of the study, the rats were sacrificed, and the hippocampus was isolated to estimate the levels of cholinergic enzymes and oxidative stress markers. Results and Discussion Memory impairment was indicated by a deficit in percentage alternation behaviour in Y-maze (p<0.05), discrimination index, escape latency and overactive cholinergic enzymes. Furthermore, the pre-treatment with polyherbal formulation improved decline and suppressed the cholinergic enzyme activity. Additionally, polyherbal formulation mitigated the effects of scopolamine injection i.e., a rise in lipid peroxidation, nitrite production, and a decrease in glutathione and superoxide dismutase levels. Conclusion These results demonstrated that polyherbal formulations can be used as an adjuvant therapy against Alzheimer’s complications by protecting the cholinergic neurons and maintaining antioxidant defence.
Keywords: Scopolamine; Cognitive impairment; Antioxidant defence; Polyherbal formulation